Sakit Rindu: Romanticization of Manthous's Songs in Commodification Practices by Dapur Musik Project - Andini, Mustika; Dienaputra, Reiza D.; Nugrahanto, Widyo (Jurnal Seni Musik, 2023)
The phenomenon of music cover in new media is now increasingly mushrooming, especially in Indonesia. Dapur Musik Project, as a keroncong music group consisting of young people, also works on cover versions of Manthous's songs, who is considered a predecessor to them. Sakit Rindu is one of Dapur Musik Project content that is most popular with the audience, as evidenced by the acquisition of million viewers. This research uses qualitative methods to analyze how Dapur Musik Project commodifies the songs composed by Manthous. In general, this research uses the framework of Adorno and Horkheimer (1944) which expresses the cultural industry theory, commodification theory put forward by Mosco (2009), and social practice theory or structural-constructive theory from Bourdieu's (1984) framework. The results of this research explain the commodification practices carried out by Dapur Musik Project in the realm of musicals and performances, as well as in the realm of packaging and marketing, with an attachment to industry and economic value. Dapur Musik Project also utilizes the symbolic power they have over relational relationships as the Manthous family in perpetuating commodification practices. The various changes in form, composition, packaging and strategy carried out by Dapur Musik Project are not considered renewal, but only a form of romanticization of Manthous's songs. Dapur Musik Project is an example of how youth people try to mediate the standardization polemic in keroncong music with their own roles and methods. This research annunciating the keroncong music community about the urgency of commodification practices in the discourse on the preservation and development of keroncong music in the Indonesian music scene.